ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI SAFETY DRIVING PADA OPERATOR FORKLIFT DI AREA KERJA WAREHOUSE PT X JAKARTA - Kalit Hidayat Budi Nugroho; Ekawati Ekawati; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Work in industries has high-risk harmful potency, in fact of the production process in using of aids for moving big material such as crane and forklift. Warehouse area of PT X has nine forklifts which consist of four battery engine and five diesel engine forklifts. The aim of this research is to analyse the factors which influence safety driving forklift operator in PT X. Method of this research is descriptivequalitative research which it combineswithcross-sectional research plan. Subject of this research consists of seven people asthe main informant and one person as triangulation informant. Result of this research shows the age and duration of work factors of forklift operator in accordance with standard operational procedure that issued by the government, forklift operator have had the knowledge of safety driving, some forklift operator are working out of procedures in operating the forklift, forklift which is used in standard and good condition, the company has to serve safety driving training and all operator have had to follow the training when making TIO/SIO process, the company have had thestandard operational procedure and socialise to forklift operator, controlled by supervisors such as reprimand and punching TIO while the operator is out of theprocedure, as a workmate is good to remind each other but to be reluctant to remind senior. This research suggests the company pays attention to the operator who works out of procedure explicitly.